Kelayakan Kanal Panampu-Jongaya Sebagai Jalur Transportasi Air di Kota Makassar - Siswono Burhan; Muhammad Yamin Jinca; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2021)
Makassar is one of the Metropolitan Cities that cannot be separated from urban problems, one of which is transportation problems. Based on data from Badan Pusat Statistik (BPS), it shows that the population growth has increased by 1.33% every year and the activities of community movements have not been accommodated due to the lack of optimal public services in solving these problems. Canal transportation is one of the alternative solutions to reduce congestion problems in the city of Makassar. The Panampu-Jongaya canal has a length of 13.7 km which protects 8 of 14 sub-districts, including: Ujung Tanah, Tallo, Bontoala, Makassar, Rappocini, Mamajang, Tamalate, and Mariso sub-districts. This study aims to see the feasibility, utilization and direction of canal development as an airway transportation route using primary and secondary data. To achieve these goals, the analysis method of canal feasibility, canal depth, canal width, vessel width, barrier-free space and environmental feasibility is used. Thus, the results of the calculation are parameters of the feasibility value of the Panampu and Jongaya canals as air transportation routes in Makassar city.